Endoscopically Assisted Marginal Mandibulectomy Using an Intraoral Approach Alone for Squamous Cell Carcinoma of the Posterior Mandibular Gingiva: A Technical Note. Issue 2 (June 2022) - Shudo, Atsushi
Study Design: Technical note. Objective: Marginal mandibulectomy is a surgical procedure for treatment of mandibular gingival tumors. The intraoral approach to the posterior region of the mandible for marginal mandibulectomy is difficult due to limited access and operating field visibility; the conventional surgical procedure may require some skin incisions. This report discusses the effectiveness of endoscopic assistance in marginal mandibulectomy. Methods: This article describes endoscopically assisted marginal mandibulectomy using an intraoral approach alone for squamous cell carcinoma of the posterior mandibular gingiva. Results: The advantages of this surgical method are twofold: (1) superior visibility to the lower edge of the mandible without any skin incision; and (2) safe surgical confirmation of important anatomy on the buccolingual side (e.g., mental foramen, lingual nerve, mandibular foramen, and neurovascular bundle). This minimally invasive approach without any skin incision, as well as the superior visibility of the operating field, are important advantages of endoscopically assisted marginal mandibulectomy that cannot be obtained by other surgical methods. Conclusions: Endoscopically assisted marginal mandibulectomy using an intraoral approach alone may be useful because it avoids damage to facial skin and improves safety by employing an enlarged bright field.